فقه الأولويات في النصيحة الشرعية : تأصيل و تطبيق - ملحم، محمد همام عبدالرحيم (عبد الفتاح محمود ادريس, 2013)
فقه أولويات النصيحة من أهم مسائل النصيحة التي ينبغي دراستها والاجتهاد فيها تأصيلاً وتطبيقاً – خصوصا في هذا العصر -؛ لأنه تتبين من خلاله مراتب النصيحة ودرجاتها، وبه يعرف ما حقه التقديم من النصائح ابتداء أو عند التعارض، وما حقه التأخير كذلك، مما يؤدي إلى ترشيد فقه النصيحة ومراعاة اختلاف الأحوال والظروف والأزمان والأماكن عند النصيحة، بما يؤدي إلى تحقيق مقاصد الشارع من شرع النصيحة. ويعرف فقه أولويات النصيحة بأنه: العلم بمراتب أعمال النصيحة ودرجات أحقياتها في تقديم بعضها على بعض، المستنبط من الأدلة ومعقولها ومقاصدها. هذا وفقه الأولويات في النصيحة شأنه شأن أي باب من أبواب الفقه، لا يمكن الاجتهاد والتوصل إلى الأحكام فيه إلا بناء على قواعد يتم الاستنباط من خلالها، وضوابط ينضبط بها الاستنباط، وهذه القواعد تمثل الجانب التأصيلي لما يمكن تسميته بميزان تصنيف أولويات النصيحة الشرعية، وهذا الميزان يقوم على ثلاث قواعد مترابطة يكمل بعضها الآخر، وهي: القواعد المقاصدية والأصولية والموضوعية، "ويقصد بالقواعد المقاصدية في تصنيف أولويات النصيحة بأنها: كل أمر كلي قطعي مستفاد من استقراء المعاني الكلية التي شرعت لأجلها النصيحة وأحكامها"، أما القواعد الأصولية في تصنيف أولويات النصيحة فهي: كل قضية كلية يتوصل بها إلى استنباط مراتب النصيحة الشرعية وأحكامها من أدلتها التفصيلية، أما القواعد الموضوعية فهي: القواعد التي تستخرج من موضوع النصيحة وطبيعتها وأركانها وشروطها وآدابها ووسائلها والأحكام التكليفية الخاصة بها. Jurisprudence of the priorities of the advice of the most important issues of advice that should be studied and diligence which Taesela and applications - especially in this day and age because it identifies which ranks advice and degrees, and has known what the right presentation of tips starting or when the conflict, and the right to delay as well, leading to rationalization advice jurisprudence and taking into account different conditions and circumstances, times and places when the advice, and this in itself leads to the achievement of the purposes of street proceeded advice. Jurisprudence defines the priorities of advice that: mattresses science business advice and degrees Ahkietha in providing each other contriver of guides, Macolha and its purposes. This and the jurisprudence of priorities in the advice like any other section of the Principles can not be diligent in it and come to terms unless it is based on the rules are elicitation through them, and controls the process of deduction, these rules represent a side Altaesela of what might be called the balance rating priorities advice legitimacy, and this Balance is based on the three bases interconnected complement each other, namely: the rules Makassed and fundamentalism and objectivity, "and is intended rules Makassed in the classification of the priorities of advice as each order total segmental learned from extrapolation of meanings college that began for her advice and provisions of' The rules of fundamentalism in the classification of the priorities of advice are: Each issue of the Faculty reach out to devise mattresses and provisions of the legal advice of detailed evidence, The substantive rules are rules that are extracted from the subject and nature of the advice and comers and conditions. \ and Literature and means and provisions of their own.
Keywords: مقاصد الشريعة الإسلامية -- أصول الفقه -- النصيحة -- الفقه الإسلامي -- الأولويات